Utilization of gasification slag and petrochemical incineration fly ash for glass ceramic production - Hao, Zhenyu; Zhang, Hai; Tang, Xiaoli; Sui, Lihua; Li, Yanan; Zhang, Shucai (Frontiers in Chemistry, 2023)
This study investigated glass ceramics produced using coal gasification slag and recycled petrochemical incineration fly ash (PIFA) to immobilize hazardous heavy metals in its amorphous-crystal multiphase structure. A low crystallization activation energy of 121.49 kJ/mol was achieved at a sintering temperature of 850 °C, implying that it is easier to produce the glass ceramics at that temperature. The Avrami parameter of the former was determined to be 1.23 ± 0.12, indicating two-dimensional crystal growth with heterogeneous nucleation. These results indicated that using gasification slag and PIFA to produce glass ceramics both facilitates their recyclability and saves energy. At 850℃, the main crystalline phases are (Ca1.96Na0.05)(Mg0.24Al0.64Fe0.12)(Si1.39Al0.61O7), Na6.65Al6.24Si9.76O32 and CaO. When the crystallization temperature rises to 1050℃, the main crystalline phases were transformed into Ca2(Mg0.25AI0.75)(Si1.25AI0.75O7) and KNa3(AlSiO4)4. The toxicity characteristic leaching procedure results indicated that the heavy metals were well solidified in the glass ceramics and that the leaching concentration was significantly lower than the limit specified by governmental agencies. The Community Bureau of Reference Sequential Extraction method was adopted to investigate the heavy-metal partitioning. The potentially toxic element index of the glass and glass ceramics sintered at 850 °C and 1050 °C were 11.7, 5.8, and 3.6, respectively. A toxicity assessment of the heavy metals conducted using the synthesis toxicity index model showed that the fly ash did not impart toxicity to the glass ceramics. Therefore, the conversion of hazardous PIFA and other solid waste into environmentally friendly glass ceramics shows considerable potential and reliability.